2016
DOI: 10.1007/s13753-016-0109-2
|View full text |Cite
|
Sign up to set email alerts
|

Measuring County Resilience After the 2008 Wenchuan Earthquake

Abstract: The catastrophic earthquake that struck Sichuan Province, China, in 2008 caused serious damage to Wenchuan County and surrounding areas in southwestern China. In recent years, great attention has been paid to the resilience of the affected area. This study applied the resilience inference measurement (RIM) model to quantify and validate the community resilience of 105 counties in the impacted area. The RIM model uses cluster analysis to classify counties into four resilience levels according to the exposure, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…5 The highest grey relational degree is the influence of TerIndO (Tertiary Industrial Output) on PM 2.5 , which is 0.96. Most of the socio-economic indicators (11 of 15) have high relational degree on PM 2.5 , near or above 0.8, except GDP (Gross Regional Domestic Product), ECPG (Energy consumption per GDP unit), SaleLGP (Sales of Liquefied Petroleum Gas), and Road (Kilometers of Urban Road).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 The highest grey relational degree is the influence of TerIndO (Tertiary Industrial Output) on PM 2.5 , which is 0.96. Most of the socio-economic indicators (11 of 15) have high relational degree on PM 2.5 , near or above 0.8, except GDP (Gross Regional Domestic Product), ECPG (Energy consumption per GDP unit), SaleLGP (Sales of Liquefied Petroleum Gas), and Road (Kilometers of Urban Road).…”
Section: Resultsmentioning
confidence: 99%
“…With China's economic rise a large number of industrial activities such as railways, highways and building construction have resulted in an increase in atmospheric particles and dust haze components of PM 2. 5 . It has been suggested that these sources, together with cer-tain weather conditions would result in a concentration of local pollutants [37,38].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using external measurement (e.g., post-disaster population increase, indicator of building reconstruction, etc.) represents a useful approach to validate the choice of variables [8,16]. The term recovery is widely used in the conceptualizations of disaster resilience [17].…”
Section: Introductionmentioning
confidence: 99%
“…It is within the context that recovery outcomes can serves as a resource and practical lessons to inform communities of the key intrinsic factors that contribute to disaster resilience [27]. Therefore, some measures tend to focus on response and recovery outcome after the damaging events for the validation of resilience measurement [8,16,28]. Based on these empirical works, useful recovery indicators and models have proved to be important decision support tools for increasing disaster resilience and reducing disaster vulnerability.…”
Section: Introductionmentioning
confidence: 99%